Джерела формування мінцкабінетів України - Сташко, Андрій (Видавництво Львівської політехніки, 2018)
The National Numismatic Fund of Ukraine was formed over the centuries through the collectible activity of museums, societies, selfless labor of professional numismatists, public figures, private collectors.
Keywords: нумізматика; мінцкабінет; музей; монета; нумізматичний предмет